Adam, Satan, and the King of Tyre: the interpretation of Ezekiel 28:11-19 in late antiquity - Patmore, Hector M. ca. 20./21. Jh. (Jewish and Christian perspectives series, 2012)
Rabbinic literature -- Church Fathers -- Targum -- The Septuagint -- The Hebrew text